Jana Pawła II apel o etyczny wymiar globalizacji - Michalak, Urszula (Annales. Etyka w Życiu Gospodarczym, 2008)
In the teaching of John Paul II’s the need of solidarity globalization is particularly stressed out aswell as that of humanization of globalization processes. With the aim of doing it, one should be guidedby unchanging social values: the truth, freedom, justice, solidarity, subsidiarity, love.The globalization has two faces:▪ the benefits which it brings to the world, individual countries and its main beneficiaries, that isinternational corporations.▪ negative effects which the developing countries and all people of the world experience (climaticchanges, emission of harmful substances, drug addiction, moral nihilism, gradual decrease ofhuman importance).It happens that complex processes caused by economical globalization make their way towardschanging a human being into an element of a market, a bartered good or a factor devoid of meaning fordecisive choices. As a consequence, a person may feel annihilated by impersonal mechanisms ona world’s scale and may gradually lose his own identity and personal dignity.Key words: